Pedagogik Berbasis Budaya Lokal Dalam Pembelajaran Seni Tari - Wiwin Purwinarti (JPKS (Jurnal Pendidikan dan Kajian Seni), 2026)
Dance learning based on local culture tends to position traditional dance merely as technical instructional content, resulting in the limited integration of its philosophical, social, and aesthetic values in the learning process. This condition leads to low levels of meaning comprehension, restricted aesthetic experience, and weak cultural awareness among students. This gap highlights the urgency of reconceptualizing regional creative dance as an ethnopedagogical framework. Therefore, this study focuses on the Banten creative dance Ringkang Jawari as both a learning source and a pedagogical framework in school dance education.